A non-invasive measurement of the knee contact force using a subject-specific musculoskeletal model to investigate osteotomy. (19th May 2018) - Badie, Fateme; Katouzian, Hamid Reza; Rostami, Mostafa
Abstract: The varus knee has been defined as a Hip-Knee-Ankle alignment of less than 180 degrees. Varus knee alignment increases the load on the medial knee and also the risk of osteoarthritis. High tibial osteotomy has been designed to modify the malalignment of varus knee. The aim of this study was to investigate the osteotomy effects on knee adduction moment (KAM) and contact forces using a musculoskeletal and subject-specific knee model. A patient with varus knee and no symptoms of any other disease or disability participated in this study. The geometry of the multibody knee model has been modified using MR images. The solutions of its finite element model have been used to determine the parameters of the multibody model. The motion data, ground reaction force and kinetic data have been applied to run the subject-specific musculoskeletal model during the stance phase of gait. After osteotomy, the adduction moment decreased, where the maximum values are comparable to other studies. The pattern of KAM did not witness any significant changes. The total and medial contact forces reduced considerably after surgery, but the lateral contact force did not significantly change. The changes in total and medial contact forces and lack of change in lateral contact force could be explained by modification of the gait pattern after surgery.